Nutritional assessment of rural villages and estates in peninsular Malaysia: total blood cholesterol values in children, adolescents and adults - Wai, Tony Ng Kock; Lin, Khor Geok; Siong, Tee E.; Hashim, Normah (Blackwell Publishing, 2001)
The present study is unique in the Malaysian context on two counts; first, it employs for the first time a functional group approach (groups based on occupational or economic activity) in the assessment of community nutritional status. Second, the study provides on a nationwide-sampling basis, information on total blood cholesterol (TC) levels in rural children (7.0-12.9 years; n = 1921) and adolescents (13.0-17.9 years; n = 753) which were hitherto unavailable. Total blood cholesterol measurements were performed on 7184 subjects ranging from 7 to 75-years-old (males = 3151; females = 4033) from households in 69 rural villages and seven estates in peninsular Malaysia, which were based on selected multistage random sampling according to the household's involvement in the following economic activities: rice farming, rubber smallholding, coconut smallholding, fishing and employment in estates. In all functional groups, TC values increased with age and there was a distinct gender effect, namely females had higher TC values than males throughout the age spectrum analyzed. Mean TC levels for children and adolescents were in the range 3.85-4.37 mmol/L, rising markedly during adulthood to an overall mean of 4.91 ± 1.13 mmol/L for men and 5.17 ± 1.11 mmol/L for women. In adults (≥ 18.0 years), there was marked disparity in mean TC values among the functional groups; males and females from rice households had the lowest mean TC values (4.58 and 4.99 mmol/L, respectively). Individuals at 'high risk' (TC > 6.20 mmol/L) averaged 16.0% in women and 11.6% in men, with women from the fishing, rubber and coconut households particularly affected (17.1-21.1%). When compared to earlier rural TC data reported for closely similar rural communities in the peninsula, the present findings suggest a 'hypercholesterolemic shift' approximating 0.39 mmol/L (15 mg/dL) in the adult population; however, this was not apparent in the children and adolescents from these rural communities.